Gender differences in the use of online platforms for political participation - Cirimele, Flavia; Macaluso, Marilena; Agolino, Giulia; Çabuk Kaya, Nilay; Zappulla, Carla (Frontiers in Communication, 2025)
IntroductionCitizens’ disengagement in political participation has become a problem in many democracies due to its negative consequences on the equal and inclusive representation of the population. However, little is known about the extent to which online platforms have become a useful tool for sustaining political participation for the most underrepresented groups (e.g., young adults and women). The present study investigates gender differences in the association between online civic participation and political participation (i.e., interest, opinion formation, and involvement) among young adults in Italy, and the mediating role of affinity with political disengagement in these associations.MethodsData were collected from 1,149 young adults (68.9% women), ranging in age from 18 to 35 years old (Mage = 25.61, SD = 4.41) by using an online survey.ResultsResults of the multiple-group (women vs. men) path analysis model evidenced that online civic engagement is directly and indirectly (through affinity with political disengagement) positively associated with high political participation, with few gender differences. Online civic participation is directly related to the ease of forming opinions in politics only for women.DiscussionOverall, findings suggest some potential benefit of online tools in reducing the gender gap in women’s participation in the political debate. Such findings may help inform the development of future programs aimed at fostering political participation among young adults.